Plan de negocios para la creación de un restaurante temático de comida internacional en la localidad de Chapinero, Bogota D.C. (2021)
The present work seeks to determine the viability and feasibility model for the creation of an International thematic Restaurant, oriented towards Italian, Peruvian and Argentine food, in the town of Chapinero, Bogotá D.C. This research exposes a differential technical model through the introduction of a concept of International food, it is It contemplates the creation of locative spaces suitable for the countries of coverage, providing the business with an infrastructure that differentiates it in terms of its commercial concept.